E-DTDOA based localization for wireless sensor networks with clock drift compensation - Vashistha, Ankush (2021)
A high time resolution localization scheme, using ultra-wide band ranging signal with bandwidth of 2GHz, is proposed for a fully asynchronous wireless sensor network (WSN). The proposed scheme is specifically useful for sensor nodes which are designed to operate at very low ADC sampling rate, in the order of 2-3 MHz, but still achieves the sampling resolution in the order of sub-nanoseconds. To achieve low sampling rate, equivalent time sampling (ETS) technique is used at the sensor nodes. Reconstructed signal obtained by ETS technique, that require periodic transmission of the same signal repetitively, is severely affected by the variation in transmitter and receiver clock drift as against the real time sampling where the variations are due to receiver node clock drift only. Thus, it requires a protocol to precisely estimate the transmitter and receiver clock parameters. A scheme, which uses a novel mathematical equivalent time of arrival (E-TOA) model for ETS based system, for clock drift estimation is presented. Based on clock drift estimation parameters, receiver nodes are tuned to the same frequency. E-TOA measurements are further used to propose an equivalent differential time difference of arrival (E-DTDOA) based ranging algorithm, which relaxed the time synchronization requirement between the wireless nodes, and still achieving high time resolution. The E-DTDOA range measurements are subsequently used to obtain precise localization of the target node/s. The feasibility of the algorithm proposed is demonstrated experimentally using in house designed wireless sensor nodes.